Placental expression of PHLDA2 and IGF2 in selective intrauterine growth restriction in monozygotic twins - Chen, Jie; Pan, Shilei; Hang, Lilin; Zhong, Mei; Yu, Yanhong (International journal of clinical and experimental pathology, 2018)
To compare the expression of imprinted genes PHLDA2 and IGF2 in the peripheral blood, placenta and fetal umbilical cord blood from normal single chorionic twins (MCDA) and single chorionic twins combined with sIUGR, in order to explore the pathogenesis relationship between the expression of PHLDA2 and IGF2 with single chorionic twins combined with sIUGR. Immunohistochemical method was applied to detect the expression of PHLDA2 and IGF2 in maternal placenta of MCDA and normal MCDA. ELISA method was applied to detect the expression of PHLDA2 and IGF2 in two groups of umbilical cord blood. There was a significant difference in two groups of maternal age and neonatal birth weight (P<0.05). Immunohistochemical results: IGF2 in the normal MCDA maternal placenta was high expression. The number of IGF2-positive cells in MCDA-sIUGR group A1 decreased slightly and the staining decreased slightly. The number of IGF2-positive cells in A2 group was significantly decreased, and the staining was weakened. In normal MCDA placenta, PHLDA2 cells were colorless, or occasionally in pale yellow; the number of PHLDA2 positive cells in MCDA sIUGR A1 group was slightly increased, the staining was light yellow or colorless. In A2 group, the number of positive cells increased significantly, the staining was brown or brownish-yellow. ELISA results showed that there were significant differences in the expression of IGF2 and PHLDA2 between cord blood of MCDA sIUGR and neonatal cord blood (P<0.05). The expression of IGF2 in MCDA sIUGR and normal MCDA twins were also significantly different (P<0.01). The differential expression of PHLDA2 and IGF2 may be one of the causes of selective intrauterine growth restriction.